Pengaruh Penggunaan Model Picture And Picture Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas IV - Nadila Swajir; Makmur Nurdin; Adnan K (STKIP Andi Matappa Pangkep, 2021)
The problem in this research is the lack of understanding of students in reading texts in Indonesian subjects so that it has an impact on student learning outcomes. This research is a descriptive quantitative research with an experimental model with the aim of knowing the effect of the model using the picture and picture model on the learning outcomes of fourth grade Indonesian students. The results showed that there was a significant effect of using the picture and picture model on the learning outcomes of fourth grade students with a t-count value (5.931) greater than t-table 2.02439, which means H0 is rejected and H1 is accepted. Based on the results of the analysis above, it can be concluded that the picture and picture model has an impact on students in understanding Indonesian reading texts so that they can improve their learning outcomes. From these conclusions, the impact resulting from this study is known that the use of the picture and picture model can improve the learning outcomes of fourth grade Indonesian students.